Legal Protection for Consumers in E-Commerce Transactions Resulting from Breaches of Contract by Businesses: A Study of the Shopee and Tokopedia Platforms - Kearen Elvira Naftali; Gunardi Lie (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of e-commerce as the primary instrument of digital commerce has transformed the legal relationships between consumers, businesses, and platform operators, thereby introducing new complexities in consumer legal protection. This study aims to analyze the concept of breach of contract in electronic transactions and examine the legal liability of marketplaces for consumer losses. The research method employed is normative legal research using a legislative and conceptual approach, supported by primary and secondary legal sources. The findings indicate that breach of contract in e-commerce encompasses non-conforming goods, delivery delays, and failure to fulfill obligations, all of which have legal implications under the Civil Code and the Consumer Protection Act. As operators of electronic systems, marketplaces bear legal liability that extends beyond that of mere intermediaries; rather, it includes active obligations to ensure transaction security. Normative reconstruction is necessary through strengthened regulations, restrictions on standard clauses, and the integration of more progressive liability principles. This study contributes to the development of legal liability theory within the digital ecosystem and provides a foundation for updating consumer protection policies in Indonesia.